PENGEMBANGAN MODEL PEMILIHAN RUTE JALAN RAYA BERDASARKAN PERILAKU PENGGUNA MENGGUNAKAN ANT-COLONY OPTIMIZATION (ACO) - Joko Siswanto (TEKNIK, 2013)
In the election of the road network usually use road network system optimization considerations with aggregative behavior by determining the shortest route or the lowest cost. Determinants of consumer behavior in route selection and decision-making of the most dominant (disaggregated). Route selection optimization model based on user behavior can be implemented from the results of model development preference with Conjoint analysis. Preferences user behavior seems, is directly proportional to the convenience, the crowd, the facilities, the ease, safety, and inversely proportional to the density. Route selection optimization model with the development of ant-colony optimization formula can be applied with the substitution probability of interaction and preferences as well as the network models incorporate the concept of route selection based on consumer behavior and the physical condition of the network.